The implementation of Computerized Maintenance Management (CMMS) in Facility Management Services (FMS) company / Muhammad Taufiq Shaharuddin - Shaharuddin, Muhammad Taufiq (Universiti Teknologi Mara, Perak, 2018)
This practical training report is important requirement and pre-requisite for the award of the Diploma in Building Surveying. This report is an investigation of ARCHIBUS system in a maintenance management company in Malaysia. This report will describes about the importance of computerized maintenance management system, the benefits of the system and many more. The increasing complexity and geographical separation of design data, tools and teams have demanded for a collaborative and distributed management environment. The CFMS is designed to manage collaborative files on WWW. Wherever remote developers are, they can navigate the evolutions and relationships between target files, check in and check out them conveniently on web browsers using CFMS.